2018
DOI: 10.1038/s41598-018-19552-2
|View full text |Cite
|
Sign up to set email alerts
|

Noise-induced bistability in the fate of cancer phenotypic quasispecies: a bit-strings approach

Abstract: Tumor cell populations are highly heterogeneous. Such heterogeneity, both at genotypic and phenotypic levels, is a key feature during tumorigenesis. How to investigate the impact of this heterogeneity in the dynamics of tumors cells becomes an important issue. Here we explore a stochastic model describing the competition dynamics between a pool of heterogeneous cancer cells with distinct phenotypes and healthy cells. This model is used to explore the role of demographic fluctuations on the transitions involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…This work has inspired the suggestion that deep connections exist between the critical threshold in RNA viruses and other transition phenomena such as cancer relapse when genomic instability grows beyond a (still to be tested) critical threshold (Solé 2003;Solé and Deisboeck 2004;Solé 2012;Castillo et al 2017). Recent mathematical and computational investigations on cancer phenotypic quasispecies (Sardanyés et al 2017Sardanyés and Alarcón 2018) have also confirmed this prediction of a critical threshold involving cancer cells extinction under genomic instability.…”
Section: Article In Pressmentioning
confidence: 76%
“…This work has inspired the suggestion that deep connections exist between the critical threshold in RNA viruses and other transition phenomena such as cancer relapse when genomic instability grows beyond a (still to be tested) critical threshold (Solé 2003;Solé and Deisboeck 2004;Solé 2012;Castillo et al 2017). Recent mathematical and computational investigations on cancer phenotypic quasispecies (Sardanyés et al 2017Sardanyés and Alarcón 2018) have also confirmed this prediction of a critical threshold involving cancer cells extinction under genomic instability.…”
Section: Article In Pressmentioning
confidence: 76%
“…Noiseinduced bistability is typically found in dynamical systems which display a single asymptotically stable state in their deterministic limit, while being able to achieve different alternative states due to stochasticity. Different examples of noise-induced stability, which can also be understood in terms of the noise-enhanced stability typical of metastable systems (see [28,29] for examples of cancer stochastic systems), have been described in many different systems [30][31][32][33]. Summarizing, we have analysed a particular scenario found in a simple model of complementary replication of viral RNAs giving rise to the so-called quasi-neutral coexistence [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Different examples of noise-induced stability, which can also be understood in terms of noise-enhanced stability typical from metastable systems (see Refs. [30,31] for examples on cancer stochastic systems) have been described in many different systems [29,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%